The Effect of Application of Revenue Recognition Based on Psak 72 on The Financial Performance of Infrastructure Companies Listed on The Idx in 2019 and 2020 - Rahman Wijaya Willyarto; Josua Panatap Soehaditama (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study is to analyze the impact of implementing revenue recognition under PSAK No. 72 on the financial performance of Indonesian infrastructure sector companies listed on the IDX in 2019 and 2020. The data used in this study was obtained from processing company financial reporting data downloaded from the site www.idx. Variables used to indicate the financial performance of a .co.id. company includes Liquidity ratio, TATO, FATO, ROA, ROE, debt ratio, and price/earnings ratio. The analytical technique used in this study is hypothesis testing using linear regression and independent sample t-tests.